The gibberellic acid on development of seedless berries in 'Isabel' grape - Tonietto, Jorge (2014)
The experiment was conducted during the vegetative cycle of 1978/79 with 'Isabel' grapevines (Vitis labrusca L.). The clusters were dipped into gibberellic acid (GA3) solutions, in prebloom or bloom time, in the concentrations of 0, 10, 50, 100, and 200 ppm. At postbloom time concentrations of 0, 50, and 100 ppm, of GA3 were utilized. Combined treatments were  still done in prebloom plus postbloom and in bloom plus postbloom. The application of GA3 in the stages of prebloom, bloom or postbloom increased the percentage of total seedless berries per cluster due to the development of normal seedless berries and small berries. This effect was greater in combined applications, in prebloom plus postbloom and with the highest concentration. All treatments reduced the seed number per normal berry. GA3 decreased the weight per cluster when applied in prebloom or in the bloom time and increased it when applied in the postbloom.